Challenges and the Overcoming Strategies in Implementation of Attorney General's Guidelines Number 18 of 2021 - Achmad Aris Mugiandono; Enggar Dian Ruhuri; Mutiara Girindra Pratiwi (Faculty of Law, Universitas Jenderal Soedirman, 2022)
The application of non-prison sentences is very minimally carried out by Law Enforcement officers so that the number of prison/detention center residents exceeds capacity (overcrowding). The Prosecutor's Office of the Republic of Indonesia through the reorientation of law enforcement policies in the implementation of The Republic of Indonesia Law Number 35 of 2009 concerning Narcotics has issued Guideline Number 18 of 2021 concerning Settlement of Handling Criminal Cases of Narcotics Abuse through Rehabilitation with a Restorative Justice Approach as an Implementation of the Dominus Litis Principle of Prosecutors which is a reference for Public Prosecutors in handling Narcotics cases so that prioritizing Rehabilitation at the Prosecution Stage which is inseparable from restorative justice. The research uses normative research methods that use secondary data in the form of scientific journals, literature, and news websites about the problem, as well as analysis based on conditions that are likely to develop about this problem. Steps that can be taken to overcome challenges in implementing the Guidelines are the need to integrate the rules for resolving cases of narcotics crimes with a Restorative Justice approach between law enforcement officers, especially Police Investigators and the Prosecutor's Office, rules that are in line with the internal rules of each law enforcement agency.Keywords: prosecutor; narcotics; restorative justice; dominus litis, challenge.